An alloy of zinc and innate immunity: Galvanising host defence against infection. (9th October 2020) - von Pein, Jessica B.; Stocks, Claudia J.; Schembri, Mark A.; Kapetanovic, Ronan; Sweet, Matthew J.
Abstract: Innate immune cells such as macrophages and neutrophils initiate protective inflammatory responses and engage antimicrobial responses to provide frontline defence against invading pathogens. These cells can both restrict the availability of certain transition metals that are essential for microbial growth and direct toxic concentrations of metals towards pathogens as antimicrobial responses. Zinc is important for the structure and function of many proteins, however excess zinc can be cytotoxic. In recent years, several studies have revealed that innate immune cells can deliver toxic concentrations of zinc to intracellular pathogens. In this review, we discuss the importance of zinc status during infectious disease and the evidence for zinc intoxication as an innate immune antimicrobial response. Evidence for pathogen subversion of this response is also examined. The likely mechanisms, including the involvement of specific zinc transporters that facilitate delivery of zinc by innate immune cells for metal ion poisoning of pathogens are also considered. Precise mechanisms by which excess levels of zinc can be toxic to microorganisms are then discussed, particularly in the context of synergy with other antimicrobial responses. Finally, we highlight key unanswered questions in this emerging field, which may offer new opportunities for exploiting innate immune responses for anti‐infective development.